Influence of Family Processes on Internet Addiction Among Late Adolescents in Hong Kong - Shek, Daniel T. L.; Zhu, Xiaoqin; Dou, Diya (Frontiers in Psychiatry, 2019)
The present study investigated how the quality of the parent–child subsystem (indexed by behavioral control, psychological control, and parent–child relationship) predicted Internet Addiction (IA) levels and change rates among senior high school students. It also examined the concurrent and longitudinal influence of the father– and mother–related factors on adolescent IA. At the beginning of the 2009/2010 school year, we randomly selected 28 high schools in Hong Kong and invited Grade 7 students to complete a questionnaire annually across the high school years. The present study used data collected in the senior high school years (Wave 4–6), which included a matched sample of 3,074 students (aged 15.57 ± .74 years at Wave 4). Growth curve modeling analyses revealed a slight decreasing trend in adolescent IA in senior high school years. While higher paternal behavioral control predicted children’s lower initial level of and a slower drop in IA, maternal behavioral control was not a significant predictor of these measures. In contrast, higher maternal but not paternal psychological control showed a significant relationship with a higher initial level of and a faster drop in adolescent IA. Finally, better father–child and mother–child relationships predicted a lower initial level of IA among adolescents. However, while poorer mother–child relationship predicted a faster decline in adolescent IA, father–child relationship quality did not. With the inclusion of all parent–child subsystem factors in the regression analyses, paternal behavioral control and maternal psychological control were identified as the two unique concurrent and longitudinal predictors of adolescent IA. The present findings delineate the essential role of parental control and the parent–child relationship in shaping children’s IA across senior high school years, which is inadequately covered in the scientific literature. The study also clarifies the relative contribution of different processes related to the father–child and mother–child subsystems. These findings highlight the need to differentiate: a) levels of and rates of change in adolescent IA, b) different family processes in the parent-child subsystem, and c) father– and mother–related factors’ contribution to adolescent IA.